Concessão de tutela provisória por decisão singular em 2º grau de jurisdição - Araújo, Telma Silva (2019)
The purpose of this study was to analyze the granting of provisional remedies by the Judge-Rapporteur at the Court of Appeal as prescribed in the Code of Civil Procedure of 2015. First, the development of the role of the Judge-Rapporteur, along with its supporting arguments, was examined. Subsequently, the duties of the Judge-Rapporteur, regulated in the article 932 of the Code of Civil Procedure, were investigated. The following chapter focused on provisional remedies and was divided in four sections. In the first section, the concept of provisional remedy as well as its main aspects were presented. The second section explored the different types of provisional remedies as prescribed in the Code of Civil Procedure. The third section was dedicated to the study of the articles of the Civil Procedure Code which regulate the granting of provisional remedy by the Judge-Rapporteur at the Court of Appeal so that a harmonious and systematic interpretation of such articles may be presented. After that, a brief analysis of the internal interlocutory appeal was carried out and conclusions were drawn